Prognostic significance of tenascin-C expression in superficial and invasive bladder cancer. Issue 9 (27th August 2004) - Brunner, A; Mayerl, C; Tzankov, A; Verdorfer, I; Tschörner, I; Rogatsch, H; Mikuz, G
Abstract : Aims: Tenascin-C (Tn-C) is an extracellular matrix glycoprotein that is upregulated in malignant tumours. Tn-C promotes cell growth, cell migration, and angiogenesis. It has been suggested to be a prognostic factor in various types of malignant tumours, but there is little information on its significance in bladder cancer with regard to overall survival (OS) and recurrence free survival (RFS). Methods: Tn-C expression was studied in 106 patients with bladder cancer diagnosed between 1994 and 1997. Immunohistochemistry was performed using a monoclonal antibody against Tn-C. RFS and OS were estimated by the Kaplan–Meier method and compared by the log rank test in univariate analysis and by the Cox multistep regression method in multivariate analysis. Results: Within the mean follow up period of 126 months, patients with diffuse Tn-C staining in the tumour stroma had a significantly worse OS than those with negative staining or only moderate Tn-C expression (p = 0.025). Patients with cytoplasmic expression of Tn-C had a significantly better OS than those without (p = 0.001). Multivariate analysis, taking into consideration age, grade, stage, tumour associated carcinoma in situ, progression, and Tn-C staining in tumour stroma, showed that only expression of Tn-C in invasive tumour cells was an independent positive prognostic factor for OS (p = 0.049). Conclusions: Tn-C may provide important prognostic information in bladder cancer depending on the expression pattern in the tumour stroma or cytoplasm of the tumour cells.